Perbedaan Kadar Trigliserida pada Millennial Vapers dan Non-Perokok di Kota Palangka Raya: Differences in Triglyceride Levels in Millennial Vapers and Non-Smokers in Palangka Raya City - Bayu Dwi Saputra; Suratno Suratno; Rita Rahmaniati; Dwi Purbayanti (Jurnal Surya Medika (JSM), 2022)
Electronic cigarettes (e-cigarettes/vape) are currently millennials' most popular tobacco or nicotine product. One of the liquid content in e-cigarettes, such as nicotine, is known to stimulate the secretion of catecholamines which can cause an increase in lipolysis in the liver. As a result, free fatty acids in the liver increase, triggering an increase in hepatic triglyceride secretion into the blood vessels. This study aimed to determine the difference in triglyceride levels in millennial vapers and non-smokers. This study uses a descriptive-analytical method with a cross-sectional approach which aims to describe or describe a situation objectively, then described. The results show that the average triglyceride level in millennial vapers is 136.5 mg/dL. While in non-smokers, 91.9 mg/dL. The Mann-Whitney test results obtained a significance value of 0.042 (p < 0.05), so it can be concluded that there is a significant difference between the results of the triglyceride level examination in millennial vapers and non-smokers.